Early history of Oriental studies at Vilnius University - Mejor, Marek (Acta Orientalia Vilnensia, 2009)
University of Warsaw The present paper was written as a contribution to the celebration of the 200th anniversary of Oriental studies at Vilnius University. The early history of Oriental studies, covering the period 1805–24, is presented on the basis of archival materials from collections kept in the Lithuanian State Historical Archives, Vilnius University Library, and Czartoryskis’ Library in Kraków. Two basic documents are published here for the first time. In the first quarter of the 19th century, three sequential attempts towards establishing a chair of Oriental studies at Vilnius University were undertaken, each one connected with a particular candidate: Szymon Żukowski (1782–1834), Julius Klaproth (1783–1835), and Józef Sękowski (1800–1858).